Single-Gene Sequencing in Newborn Screening: Success, Challenge, Hope - Currier, Robert J. (The Hastings Center report, 2018)
Some state-based newborn screening programs in the United States already use sequencing technology, as a secondary screening test for individual conditions rather than as a broad screening tool. Newborn screening programs sequence an individual gene, such as the cystic fibrosis transmembrane conductance regulator, which causes cystic fibrosis, after an initial biochemical test suggests that a baby might have a condition related to that gene. The experiences of state public health departments with individual-gene sequencing illustrate both the usefulness of the technology and its complexities. Here I discuss how newborn screening programs investigate cystic fibrosis and, as another example, adrenoleukodystrophy through individual gene sequencing.